2006
DOI: 10.1038/ncb1426
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic and tumour suppressor activity of a novel Beclin1-binding protein UVRAG

Abstract: Autophagy, the degradation of cytoplasmic components, is an evolutionarily conserved homeostatic process involved in environmental adaptation, lifespan determination and tumour development. The tumor suppressor Beclin1 is part of the PI(3) kinase class III (PI(3)KC3) lipid-kinase complex that induces autophagy. The autophagic activity of the Beclin1-PI(3)KC3 complex, however, is suppressed by Bcl-2. Here, we report the identification of a novel coiled-coil UV irradiation resistance-associated gene (UVRAG) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
894
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 940 publications
(931 citation statements)
references
References 38 publications
22
894
4
3
Order By: Relevance
“…Different binding interactions for the BH3-domain of Beclin-1 bound to Bcl-xL compared with other BH3-domains were also reported (Feng et al, 2007;Oberstein et al, 2007). Moreover, Beclin-1 is bound to many other proteins in addition to Bcl-2 family members (Vps34 (Furuya et al, 2005), UVRAG (Liang et al, 2006;Takahashi et al, 2007), Bif1 (Takahashi et al, 2007) Ambra (Fimia et al, 2007)), which may further obscure the function of the BH3-domain. It is interesting to note that UVRAG was recently reported to modulate the stoichiometry of Beclin-1 binding to Bcl-2/xL (Noble et al, 2008;Samara et al, 2008), but the impact on apoptosis is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Different binding interactions for the BH3-domain of Beclin-1 bound to Bcl-xL compared with other BH3-domains were also reported (Feng et al, 2007;Oberstein et al, 2007). Moreover, Beclin-1 is bound to many other proteins in addition to Bcl-2 family members (Vps34 (Furuya et al, 2005), UVRAG (Liang et al, 2006;Takahashi et al, 2007), Bif1 (Takahashi et al, 2007) Ambra (Fimia et al, 2007)), which may further obscure the function of the BH3-domain. It is interesting to note that UVRAG was recently reported to modulate the stoichiometry of Beclin-1 binding to Bcl-2/xL (Noble et al, 2008;Samara et al, 2008), but the impact on apoptosis is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the autophagy related gene, Atg5, has been reported to suppress tumor genesis in a mouse xenograft model [27] . More interestingly, the expression of both Beclin 1 and UVRAG has been shown to repress the growth of human cancer cell xenografts [28] . Thus, although the molecular mechanisms are poorly understood, it is reasonable to postulate the importance of autophagy in tumor suppression.…”
Section: Autophagic Flux Defects In Cancermentioning
confidence: 99%
“…Nucleation of the autophagic vesicle involves a Type III PI3 kinase complex that includes the kinase (Vps34) and Beclin1 (Atg6), which interact through a conserved domain in Beclin 1 (33). This complex contains multiple proteins including another putative tumor suppressor called UVRAG (34) and a protein called Ambra1 (35) , which regulate the activity of the kinase and thus control autophagy induction. Recently it was demonstrated that another protein called Bif-1 binds to UVRAG and that this interaction can also regulate the PI3 kinase activity and induce autophagic vesicle formation (36).…”
Section: Regulation Of Autophagymentioning
confidence: 99%